Sanksi Bagi Pemberi Dan Penerima Gratifikasi Perspektif Hukum Pidana Islam - Andiko, Toha (UIN Fatmawati Sukarno Bengkulu, 2016)
Abstract: “Sanctions for Givers and Recipients of Gratification Based on Islamic Criminal Law.” In various Hadith literature, the status of gratification perpetrator has not been fully explained. This can be seen from differences among scholars whether it is included into bribery or a halal gift. On the other hand the status of bribes and giving prizes is clear enough, unlike the status of gratification which still in debate among scholars. Similarly, sanctions for the perpetrators of gratification are not mentioned explicitly. The sanctions are more dominated by moral aspect that still needs further interpretation. The results of this study conclude that gratification in the sense of giving prizes in the form of money, bonuses or other services that are lawful to officers or officials is essentially legal as long as there is no agreement in the beginning, not excessive, and not given in advance (before the affairs are completed). However, the sanctions for those perpetrators of gratification in the sense of giving the prizes promised at the initial term, or granted before the completion of the affairs, in Islamic criminal law those givers and the recipients may be subject to punishment or in Islam known as takzir (the form and size of the punishment shall be submitted to an official judge appointed by the legitimate government).